Effectiveness of Bioactive Toothpastes against Dentin Hypersensitivity Using Evaporative and Tactile Analyses: A Randomized Clinical Trial - Alonso, Roberta Caroline Bruschi (2024)
The objective of this study was to investigate and compare the effectiveness of toothpastes containing bioactives to relieve dentin hypersensitivity with that of a commercial desensitizing toothpaste containing REFIX technology, associated or not with a calcium booster. In this double-blind, randomized, parallel-group, multi-center clinical trial, thirty-two volunteers diagnosed with dentin hypersensitivity and qualified to participate were randomized into four groups: (1) Colgate Sensitive Pro-Relief; (2) Sensodyne Repair & Relief; (3) Regenerador Sensitive; and (4) Regenerador Sensitive, associated with a calcium booster. Evaporative and tactile tests were used to check for dentin hypersensitivity in the test subjects. The participants brushed their teeth with one of the toothpastes, and dentin hypersensitivity was immediately tested using a visual analogue scale (VAS), in which the pain was rated on a scale of 0 to 10. Dentin hypersensitivity was measured after one week and after one month of the subjects continuing to use the toothpaste three times per day. Data were statistically analyzed with a non-parametric Friedman test for dependent data (alpha = 0.05). All toothpastes reduced dentin hypersensitivity. In the evaporative test, Sensodyne Protect & Repair and Regenerador Sensitive, associated with the calcium booster, exhibited faster and more effective results in reducing pain caused by dentin hypersensitivity, even after the first use. Colgate Sensitive Pro-Relief was effective only after one week of use. All toothpastes performed well in the tactile test for treating dentin hypersensitivity, and their performance improved over time. Sensodyne Repair & Protect presented the highest overall pain remission after one month (84.6%). The bioactive toothpastes reduced, to a different extent, the tooth hypersensitivity reported by the volunteers. Sensodyne Repair & Relief and Regenerador Sensitive, associated or not with a calcium booster, presented faster and more effective results in reducing pain caused by dentin hypersensitivity.